A method for preparing fiber-reinforced metal ceramic material

By pretreating silicon carbide fibers and specific process treatment with titanium cermet powder, fiber-reinforced cermet materials are prepared, which solves the problem of uneven microstructure of metal cermet materials in the prior art, significantly improves the overall performance of the material, and is suitable for high-performance needs in the aviation field.

CN119243060BActive Publication Date: 2025-03-04YOUCAITEC MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411788122.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing metal cermet material preparation process is difficult to accurately control the distribution and grain size of each phase in the matrix, resulting in uneven microstructure of the material and affecting its comprehensive performance.

Method used

A method for preparing fiber-reinforced metal cermet materials is adopted, including pretreatment of silicon carbide fibers, mixing titanium metal powder and silicon carbide ceramic powder, and obtaining fiber-reinforced metal cermet materials through ultrasonic mixing, cold isostatic molding, hot pressing molding, low-temperature presintering, high-temperature sintering and other process steps, combining argon atmosphere protection and magnetic field-assisted sintering, and finally obtaining fiber-reinforced metal cermet materials through ion implantation and annealing treatment.

Benefits of technology

The strength, toughness, hardness, high temperature resistance, wear resistance and corrosion resistance of the material are significantly improved, and the comprehensive performance is better than that of the materials prepared in the prior art, which can better meet the high performance requirements in the aviation field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243060B_ABST
    Figure CN119243060B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of material preparation, and aims to solve the problem that the preparation process of the existing metal ceramic material is difficult to accurately control the distribution and grain size of each phase in the metal ceramic matrix, resulting in uneven microstructure of the material, thereby affecting the comprehensive performance of the material. To this end, the present invention provides a method for preparing a fiber-reinforced metal ceramic material, comprising: pre-treating silicon carbide fiber; mixing and grinding titanium metal powder and silicon carbide ceramic powder according to a predetermined ratio; then adding silicon carbide fiber particles and placing them in an ultrasonic mixer; adding a dispersant and a binder and mixing them again; the mixture is sequentially cold isostatically pressed and hot pressed; the obtained blank is sequentially pre-sintered, high-temperature sintered, cut and surface treated. The metal ceramic material prepared by the present invention is significantly improved in strength, toughness, hardness, high temperature resistance, wear resistance and corrosion resistance, can better meet the high performance requirements in the aviation field, and provide strong support for the aviation industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation, and in particular to a method for preparing a fiber-reinforced metal ceramic material. Background Art

[0002] In the modern industrial field, the performance and quality of materials often determine the performance and reliability of products. With the continuous advancement of science and technology, various new materials emerge in an endless stream, and material preparation technology is also constantly innovating and developing. Although traditional material preparation methods can meet the needs of production and life to a certain extent, they are gradually showing some limitations in the face of increasingly complex and diversified application scenarios. In many fields, the requirements for material strength, hardness, toughness, high temperature resistance, corrosion resistance and other properties are getting higher and higher. Traditional single materials are often difficult to have these excellent comprehensive properties at the same time. In order to overcome this problem, the research and preparation of composite materials has gradually become a hot spot in the field of materials. Composite materials combine two or more materials with different properties to give full play to their respective advantages, thereby obtaining better performance than single materials.

[0003] For example, in the field of aviation materials, the aviation industry, as a high-end field of modern industry, has extremely stringent requirements on the performance of materials. Aircraft need to withstand extremely harsh environmental conditions such as high temperature, high pressure, high stress, and high corrosion during flight. Therefore, aviation materials must have excellent performance to ensure the safety, reliability and efficient operation of aircraft. In terms of strength, aviation materials need to have sufficient strength to withstand various loads during flight, including the weight of the fuselage structure, aerodynamic load, engine thrust, etc. At the same time, the material also needs to have good toughness to prevent fracture when it is impacted or vibrated. High temperature resistance is another key performance requirement of aviation materials. In the engine part of the aircraft and the high temperature area generated by friction with the air during high-speed flight, the material needs to be able to maintain its mechanical properties and physical and chemical stability at high temperatures without softening, deformation or oxidation. In addition, aviation materials also need to have good corrosion resistance to resist the corrosion of oxygen, moisture, pollutants and fuel in the atmosphere. At the same time, in order to meet the needs of lightweight aviation aircraft, the material should also have a lower density. However, to meet these numerous and strict performance requirements at the same time, traditional material preparation methods and existing material systems face huge challenges.

[0004] As a commonly used aviation material, the microstructure of the metal-ceramic matrix has an important influence on the performance of the material. However, the existing preparation process makes it difficult to accurately control the distribution and grain size of each phase in the metal-ceramic matrix, resulting in an uneven microstructure of the material, which will affect the stability and consistency of the mechanical, thermal and chemical properties of the material. For example, the uneven microstructure will cause the strength and oxidation resistance of the material to decrease at high temperatures, and it is prone to local deformation or fracture when subjected to external forces.

[0005] In view of this, the art needs a method for preparing a fiber-reinforced metal-ceramic material to solve the above problems. Summary of the invention

[0006] In order to solve the above technical problems, that is, to solve the problem that the existing preparation process of metal ceramic materials is difficult to accurately control the distribution and grain size of each phase in the metal ceramic matrix, resulting in uneven microstructure of the material and thus affecting the comprehensive performance of the material.

[0007] The present invention provides a method for preparing a fiber-reinforced metal ceramic material, the preparation method comprising:

[0008] S1: pretreating silicon carbide fibers and finally obtaining silicon carbide fiber particles;

[0009] S2: mixing and grinding titanium metal powder and silicon carbide ceramic powder according to a predetermined ratio to obtain metal ceramic powder;

[0010] S3: putting the metal ceramic powder and the silicon carbide fiber particles into an ultrasonic mixer for mixing;

[0011] S4: adding a dispersant and a binder to the mixture obtained in step S3, mixing and grinding again;

[0012] S5: performing cold isostatic pressing and hot pressing on the mixture obtained in step S4 in sequence, wherein argon gas is used as an atmosphere protection during the hot pressing process;

[0013] S6: placing the hot-pressed green body into a tubular furnace and performing low-temperature pre-sintering in an argon atmosphere;

[0014] S7: placing the pre-sintered green body into a hot isostatic pressing sintering furnace and sintering at high temperature under an argon atmosphere, and then slowly cooling the green body to room temperature in the sintering furnace;

[0015] S8: Cut and polish the cooled material, then implant nitrogen ions into the material surface by ion implantation and perform annealing to finally obtain a fiber-reinforced metal-ceramic material.

[0016] In some preferred embodiments, step S1 specifically includes:

[0017] S11: soaking the silicon carbide fiber in a hydrofluoric acid solution;

[0018] S12: After the immersion, the silicon carbide fiber is thoroughly rinsed with deionized water, and then dried;

[0019] S13: placing the dried silicon carbide fiber in a chemical vapor deposition furnace, and performing chemical vapor deposition at a high temperature using trichloromethylsilane and hydrogen as reaction gases to deposit a silicon carbide coating on the surface of the silicon carbide fiber;

[0020] S14: preparing a sol solution containing tetraethyl orthosilicate, ethanol and water in a predetermined ratio, soaking the silicon carbide fiber after chemical vapor deposition in the sol solution, and then drying and heat treating to convert the sol into a silicon dioxide coating, wherein in step S14, the soaking step to the heat treatment step are repeated 2-4 times;

[0021] S15: placing the silicon carbide fiber coated with the silicon carbide coating and the silicon dioxide coating into a tube furnace and performing a high temperature annealing treatment in an argon atmosphere;

[0022] S16: Grinding the silicon carbide fibers after high temperature annealing into silicon carbide fiber particles.

[0023] In certain preferred embodiments, in step S11, the concentration of the hydrofluoric acid solution is 8-12%, and the immersion time is 25-35 minutes;

[0024] In step S12, the drying temperature is 75-90°C and the drying time is 1.8-2.2 hours;

[0025] In step S13, the temperature of the high temperature treatment is 1000-1300° C., the gas flow ratio of trichloromethylsilane and hydrogen is 1:(8.5-12), and the chemical vapor deposition time is 1.5-3 hours;

[0026] In step S14, the molar ratio of tetraethyl orthosilicate, ethanol and water is 1:(8-12):(4-6), the soaking time is 0.5-1.5 hours, the drying time in air is 10-13 hours, and the heat treatment temperature is 580-680°C;

[0027] In step S15, the high temperature annealing temperature is 950-1050°C, and the holding time is 1.8-2.3 hours.

[0028] In some preferred embodiments, step S2 specifically includes:

[0029] S21: mixing titanium metal powder and silicon carbide ceramic powder in a mass ratio of 40:60;

[0030] S22: putting the mixed powder into a ball mill for ball milling. The ball milling time is 11-12 hours. The rotation speed of the ball mill is 280-330 r / min. The ball-to-material ratio is (4.7-5.5):1.

[0031] In certain preferred embodiments, in step S3, the volume fraction of the metal ceramic powder is 80-82%, the volume fraction of the silicon carbide fiber particles is 18-20%, the mixing time of the metal ceramic powder and the silicon carbide fiber particles in the ultrasonic mixer is 1-1.2 hours, and the ultrasonic power is 1000-1200W.

[0032] In certain preferred embodiments, in step S4, the mass fraction of the mixture obtained in step S3 is 95.5-97%, the mass fraction of the dispersant is 1-1.5%, and the mass fraction of the binder is 2-3%, wherein the dispersant is polyvinyl alcohol and the binder is phenolic resin;

[0033] Step S4 specifically includes:

[0034] S41: adding a dispersant and a binder to the mixture obtained in step S3;

[0035] S42: The mixture obtained in step S41 is put into a ball mill and ball milled again for 6-7 hours. The rotation speed of the ball mill is 200-250 r / min and the ball-to-material ratio is 3:1.

[0036] In certain preferred embodiments, in step S5, the mixture obtained in step S4 is subjected to cold isostatic pressing using a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine is 180-210 MPa, and the holding time is 5-7 minutes; and / or,

[0037] In step S5, a hot pressing molding machine is used to hot press the material after cold isostatic pressing, wherein the hot pressing temperature of the hot pressing molding machine is 1500-1600° C., the hot pressing pressure is 50-55 MPa, and the insulation time is 1.5-2 hours.

[0038] In certain preferred embodiments, in step S6, the pre-sintering temperature of the tube furnace is 800-900° C., and the holding time is 2-2.5 hours; and / or,

[0039] In step S7, the sintering temperature of the hot isostatic pressing furnace is 1800-2000°C, the pressure is 100-120 MPa, and the holding time is 4-5 hours.

[0040] In certain preferred embodiments, a magnetic field generating device is provided in both the tubular furnace and the hot isostatic pressing sintering furnace. During the pre-sintering and high-temperature sintering of the green body, the magnetic field strength generated by the magnetic field generating device is 0.5-2 Tesla.

[0041] In some preferred embodiments, in step S8, the energy of the ion implantation is 100-110 keV and the dose is 1×10¹ 7 ions / cm².

[0042] The present invention has the following beneficial effects:

[0043] In terms of fiber processing and reinforcement effect, the present invention pre-treats silicon carbide fibers to effectively remove surface impurities and oxide layers, laying a foundation for subsequent coating adhesion and good bonding with the metal ceramic matrix, improving the interface bonding strength between the fiber and the matrix, better exerting the fiber reinforcement effect, and improving the overall strength and toughness of the material; processing the fibers into granular form increases the contact area with the metal ceramic powder, improves dispersion uniformity, reduces agglomeration and local stress concentration, and makes the material performance more stable and reliable; through a specific process, the metal ceramic powder and silicon carbide fiber particles are fully mixed and tightly combined, and the fiber-reinforced structure can effectively transfer loads, prevent crack propagation, absorb dispersed energy, and greatly improve the fracture toughness of the material. In terms of material preparation process and microstructure optimization, the ultrasonic mixer makes the metal ceramic powder and silicon carbide fiber particles evenly mixed on a micro scale to ensure the consistency of the macroscopic properties of the material; cold isostatic pressing is combined with hot pressing. Cold isostatic pressing makes the material fill the mold evenly to reduce pore defects. Hot pressing is carried out under the protection of argon atmosphere. High temperature and high pressure densify the material and tightly combine the particles, thereby improving the density, strength and microstructure uniformity and comprehensively improving the mechanical and physical properties; low-temperature pre-sintering and high-temperature sintering are carried out in steps to remove organic matter and moisture from the green body. Low-temperature pre-sintering forms a structural framework that is conducive to high-temperature sintering densification and performance improvement. The high temperature in the hot isostatic pressing furnace During warm sintering under argon atmosphere, high pressure makes the particles diffuse and fuse fully, eliminates pore defects, makes the organizational structure uniform and stable, and significantly improves performance indicators such as density, strength, hardness, and wear resistance; post-processing cutting and surface polishing make the material size precise and the surface smooth, improve the appearance quality and dimensional accuracy, reduce friction resistance and wear, and extend the service life; ion implantation technology implants nitrogen ions on the material surface to change the surface chemical composition and organizational structure, improve surface hardness, wear resistance, and corrosion resistance, and annealing treatment eliminates injection defects, stabilizes the surface structure, and enhances surface performance, so that the material resists erosion and wear in a complex aviation environment, ensuring reliability and stability. Through the above-mentioned overall preparation process, the fiber-reinforced metal ceramic material prepared by the present invention is significantly improved in strength, toughness, hardness, high temperature resistance, wear resistance, and corrosion resistance. The comprehensive performance is better than that of the material prepared by the prior art, which can better meet the high-performance requirements in the aviation field, and is suitable for a variety of aviation parts in the aviation field, providing strong support for the aviation industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings:

[0045] Figure 1 The present invention is a flow chart of the method for preparing the fiber-reinforced metal ceramic material. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0047] Based on the problem pointed out in the background technology that it is difficult to accurately control the distribution and grain size of each phase in the metal ceramic matrix in the preparation process of the existing metal ceramic materials, resulting in uneven microstructure of the material and thus affecting the comprehensive performance of the material, the present invention provides a method for preparing a fiber-reinforced metal ceramic material, aiming to significantly improve the strength, toughness, hardness, high temperature resistance, wear resistance and corrosion resistance of the prepared metal ceramic material, so as to better meet the high performance requirements in the aviation field and provide strong support for the aviation industry.

[0048] like Figure 1 As shown, the preparation method of the fiber-reinforced metal ceramic material provided by the present invention comprises:

[0049] S1: pretreating silicon carbide fibers and finally obtaining silicon carbide fiber particles;

[0050] Preferably, step S1 specifically includes:

[0051] S11: Soak the silicon carbide fiber in a hydrofluoric acid solution with a concentration of 8-12% for 25-35 minutes. Hydrofluoric acid is highly corrosive and can effectively remove impurities and oxide layers on the fiber surface, providing a good foundation for the subsequent coating adhesion.

[0052] S12: After soaking, the silicon carbide fiber is thoroughly rinsed with deionized water to remove the hydrofluoric acid and impurities remaining on the fiber surface, and then the silicon carbide fiber is placed in an oven and dried at a temperature of 75-90° C. for 1.8-2.2 hours to ensure that the moisture on the surface of the silicon carbide fiber is completely evaporated and in a dry state, which is convenient for subsequent processing steps;

[0053] S13: placing the dried silicon carbide fiber in a chemical vapor deposition furnace, using trichloromethylsilane (MTS) and hydrogen as reaction gases at a high temperature of 1000-1300°C for chemical vapor deposition for 1.5-3 hours, with a gas flow ratio of trichloromethylsilane (MTS) to hydrogen being 1:(8.5-12), so as to deposit a 0.3-0.8 μm silicon carbide coating on the surface of the silicon carbide fiber, which can further enhance the performance of the fiber, improve its wear resistance, oxidation resistance, etc., and is also conducive to better bonding with the metal ceramic matrix;

[0054] S14: a sol solution containing tetraethyl orthosilicate, ethanol and water is prepared in a molar ratio of 1:(8-12):(4-6), and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 0.5-1.5 hours to allow the fiber to fully absorb the sol, and then dried in air for 10-13 hours to allow the solvent in the sol to evaporate and initially form a coating, and then heat treated at a temperature of 580-680°C to convert the sol into a silicon dioxide coating, wherein in step S14, the immersion step to the heat treatment step is repeated 2-4 times, preferably 3 times, so as to increase the thickness and uniformity of the coating, and the silicon dioxide coating can improve the chemical stability and high temperature resistance of the fiber, and cooperate with the silicon carbide coating to further improve the comprehensive performance of the fiber;

[0055] S15: putting the silicon carbide fiber coated with the silicon carbide coating and the silicon dioxide coating into a tube furnace, and performing high temperature annealing treatment in an argon atmosphere. The high temperature annealing temperature is 950-1050°C, and the holding time is 1.8-2.3 hours. The argon atmosphere can prevent the fiber from being oxidized at high temperature. The annealing treatment can improve the bonding state between the coating and the fiber, increase the bonding strength, reduce the defects in the coating, make the fiber more stable and reliable in the subsequent use process, and better play the reinforcing role;

[0056] S16: Grinding the silicon carbide fibers after high temperature annealing into silicon carbide fiber particles.

[0057] S2: Mix and grind titanium metal powder and silicon carbide ceramic powder in a predetermined ratio to obtain metal ceramic powder. Titanium metal has good toughness and machinability, which enables the material to have certain deformation ability and easy processing characteristics during molding and use; silicon carbide ceramic has high hardness, high strength and high temperature resistance, which can improve the overall strength and high temperature resistance of the material. The combination of the two is expected to obtain metal ceramic materials with excellent comprehensive performance, which can meet the requirements of high performance materials in aviation and other fields;

[0058] Preferably, step S2 specifically includes:

[0059] S21: mixing titanium metal powder and silicon carbide ceramic powder in a mass ratio of 40:60;

[0060] S22: putting the mixed powder into a ball mill for ball milling, the ball milling time is 11-12 hours, the rotation speed of the ball mill is 280-330r / min, and the ball-to-material ratio is (4.7-5.5):1. During the ball milling process, the rotation of the ball mill drives the ball-to-material movement, so that the powders constantly collide and rub against each other, thereby achieving uniform mixing. The uniformly mixed metal ceramic powder lays a foundation for subsequent mixing with fibers and the molding and performance of the material;

[0061] S3: Put the metal ceramic powder and silicon carbide fiber particles into an ultrasonic mixer for mixing. The volume fraction of the metal ceramic powder is 80-82%, and the volume fraction of the silicon carbide fiber particles is 18-20%. The mixing time is 1-1.2 hours. The ultrasonic power of the ultrasonic mixer is 1000-1200W. Silicon carbide particles have the characteristics of small size and large specific surface area, which can play a role in refining grains, thereby improving the strength and toughness of the material. Ultrasonic waves generate high-frequency vibrations in the mixture, so that the fibers can be evenly dispersed in the powder to avoid fiber agglomeration. The uniform dispersion of fibers is crucial to improving the overall performance of the material, and can enable the fibers to better play a reinforcing role in the material.

[0062] S4: adding a dispersant and a binder to the mixture obtained in step S3, mixing and grinding again, wherein the mass fraction of the mixture obtained in step S3 is 95.5-97%, the mass fraction of the dispersant is 1-1.5%, and the mass fraction of the binder is 2-3%, wherein the dispersant is polyvinyl alcohol and the binder is phenolic resin;

[0063] Preferably, step S4 specifically includes:

[0064] S41: adding a dispersant and a binder to the mixture obtained in step S3, wherein the dispersant helps to further improve the dispersion uniformity of the powder and the fiber in the mixed system and prevent reagglomeration, and the binder can play a bonding role in the subsequent molding process, so that the material blank has a certain initial strength;

[0065] S42: The mixture obtained in step S41 is placed in a ball mill and ball-milled again for 6-7 hours. The rotation speed of the ball mill is 200-250r / min, and the ball-to-material ratio is 3:1. Through ball-milling again, the additive is fully mixed with the powder and fiber to ensure that the additive can be evenly distributed in the entire mixing system to play its due role and provide good material preparation for the subsequent molding process.

[0066] S5: performing cold isostatic pressing and hot pressing on the mixture obtained in step S4 in sequence, wherein argon gas is used as an atmosphere protection during the hot pressing process;

[0067] Preferably, in step S5, a cold isostatic pressing machine is used to perform cold isostatic pressing on the mixture obtained in step S4, wherein the set molding pressure of the cold isostatic pressing machine is 180-210 MPa, and the holding time is 5-7 minutes. Under the action of high pressure, the gaps between the material particles are reduced, the density uniformity of the blank is improved, and a certain initial strength can also be obtained. The advantage of cold isostatic pressing is that pressure can be applied more evenly, reducing stress concentration and defects inside the blank, and providing a good quality blank for the subsequent hot forming process.

[0068] Preferably, in step S5, a hot pressing molding machine is used to hot press the material after cold isostatic pressing, wherein the hot pressing temperature of the hot pressing molding machine is 1500-1600°C, the hot pressing pressure is 50-55MPa, and the insulation time is 1.5-2 hours. During the hot pressing process, argon atmosphere protection is used to prevent the material from oxidizing at high temperature. The combined effect of high temperature and high pressure makes the material further densified, and the particles are more tightly bonded, thereby improving the performance of the material. The argon atmosphere can isolate the air, avoid chemical reaction between the material and oxygen, and ensure the purity and performance stability of the material.

[0069] S6: The hot-pressed green body is placed in a tubular furnace and pre-sintered at low temperature under an argon atmosphere. The pre-sintering temperature of the tubular furnace is 800-900°C, and the holding time is 2-2.5 hours. Low-temperature pre-sintering helps to remove organic matter and moisture in the green body. At a temperature of 800-900°C, the organic matter will decompose and volatilize, and the moisture will also be evaporated to prepare for high-temperature sintering. At the same time, low-temperature pre-sintering can also make some components in the green body react initially to form a certain structural framework, which is beneficial to the densification and performance improvement of the material during high-temperature sintering.

[0070] S7: The pre-sintered green body is placed in a hot isostatic pressing sintering furnace and sintered at high temperature under an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace. The sintering temperature of the hot isostatic pressing sintering furnace is 1800-2000°C, the pressure is 100-120MPa, and the insulation time is 4-5 hours. During the high-temperature sintering process, argon atmosphere protection is also used to prevent material oxidation. The high temperature and high pressure environment can make the material particles fully diffuse and fuse, and the material is denser, thereby significantly improving the material's performance, such as strength, hardness, wear resistance, etc. Hot isostatic pressing sintering can effectively eliminate the pores and defects inside the material, making the material's organizational structure more uniform and stable, further improving the material's comprehensive performance, and meeting the requirements of high-performance materials in high-end fields such as aviation.

[0071] Preferably, a magnetic field generating device is provided in both the tubular furnace and the hot isostatic pressing sintering furnace. During the pre-sintering and high-temperature sintering of the green body, the magnetic field generating device generates a magnetic field strength of 0.5-2 Tesla. After repeated experiments, comparisons and analyses by the inventors, it is found that if the magnetic field strength is lower than 0.5 Tesla, sufficient Lorentz force cannot be generated on the charged particles in the material, and it is difficult to achieve the purpose of inducing crystal structure adjustment and reducing defects. In actual preparation, the direction of the magnetic field is set to be parallel to or the same as the growth direction of the crystal, so that the crystal grows more orderly. For example, for material components in aviation parts that need to withstand unidirectional tensile force, the direction of the magnetic field is set to be the same as the direction of the tensile force. In this way, during the magnetic field-assisted sintering process, the crystal structure in the material will grow more orderly along the direction of the magnetic field (that is, the direction of the tensile force), thereby better resisting the tensile stress. At the same time, the action time of the magnetic field matches the time of the sintering process. In the high-temperature sintering stage, the temperature is 1800-2000°C and the insulation time is 4-5 hours. The magnetic field can continue to act during the entire insulation time. In this high-temperature stage, the material particles are in an active diffusion and fusion state. The continuous action of the magnetic field helps to guide the orderly arrangement of the crystal structure during the material densification process.

[0072] Further preferably, at the beginning of sintering, when the material just starts to heat up and the particles begin to initially combine, a weaker magnetic field (0.5-1 Tesla) is first applied for a short time (the first 1-2 hours) to help the material form a preliminary ordered structure, and then at the end of sintering (after 1-2 hours), the magnetic field strength is increased (1-2 Tesla) and continued until the end of sintering to further optimize the crystal structure and make the material more dense and uniform. This way of setting the magnetic field parameters in segments can more finely control the microstructure evolution process of the material and improve the material performance. Specifically, in the above, the initial sintering period can be 0-1 hours, and the later sintering period can be 1-4 hours, or the initial sintering period is 2 hours and the later sintering period is 2-5 hours.

[0073] S8: cutting and surface polishing the cooled material, then implanting nitrogen ions into the surface of the material by ion implantation and then annealing, to finally obtain a fiber-reinforced metal-ceramic material;

[0074] Preferably, the material is cut into a suitable length and width by a cutting process, and the surface of the material is ground by a grinding process to make the surface smoother. During the processing, a low-stress processing method is used, such as electrospark processing or laser processing. The low-stress processing method can avoid introducing stress and damaging the material surface, and ensure that the performance of the material is not affected by the processing process. After the processing is completed, polishing is performed to further improve the surface quality of the material, make the surface smoother, reduce the surface roughness, and improve the appearance and performance of the material. Ion implantation technology is used to implant nitrogen ions on the surface of the material. The energy of the ion implantation is 100-110keV and the dose is 1×10¹ 7 ions / cm², the injection of nitrogen ions can change the chemical composition and organizational structure of the material surface, thereby improving the hardness, wear resistance and corrosion resistance of the material. After injection, the material is annealed in a vacuum furnace. The annealing temperature and time are determined according to the material properties and process requirements. The annealing treatment can eliminate the defects generated during the injection process, making the structure of the material surface more stable and the performance more superior. Through surface strengthening treatment, the surface properties of the material can be significantly improved, the service life of the material can be extended, and the use requirements in complex environments can be met.

[0075] The technical solution of the present invention is further described below through a plurality of embodiments and comparative examples.

[0076] Embodiment 1

[0077] The silicon carbide fiber was immersed in a hydrofluoric acid solution with a concentration of 8% for 25 minutes; the silicon carbide fiber after immersion was thoroughly rinsed with deionized water, and then the silicon carbide fiber was placed in an oven and dried at a temperature of 75°C for 1.8 hours; the silicon carbide fiber after drying was placed in a chemical vapor deposition furnace, and trichloromethylsilane (MTS) and hydrogen were used as reaction gases for chemical vapor deposition at a high temperature of 1000°C for 1.5 hours, and the gas flow ratio of trichloromethylsilane (MTS) to hydrogen was 1:8.5; according to the molar ratio of 1:8:4 A sol solution containing tetraethyl orthosilicate, ethanol and water is prepared, and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 0.5 hour, and then dried in air for 10 hours, and then heat treated at a temperature of 580°C, and the steps of immersion, drying and heat treatment are repeated twice; the silicon carbide fiber coated with silicon carbide coating and silicon dioxide coating is placed in a tubular furnace, and high-temperature annealing treatment is performed in an argon atmosphere, the high-temperature annealing temperature is 950°C, and the insulation time is 1.8 hours; the silicon carbide fiber after high-temperature annealing is ground into silicon carbide fiber particles.

[0078] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is placed in a ball mill for ball milling, the ball milling time is 11 hours, the speed of the ball mill is 280r / min, and the ball-to-material ratio is 4.7:1; the metal ceramic powder and silicon carbide fiber particles are placed in an ultrasonic mixer for mixing, the volume fraction of the metal ceramic powder is 80%, the volume fraction of the silicon carbide fiber particles is 20%, the mixing time is 1 hour, and the ultrasonic power of the ultrasonic mixer is 1000W; polyvinyl alcohol and phenolic resin are added to the obtained mixture, the mass fraction of the mixture is 95.5%, the mass fraction of polyvinyl alcohol is 1%, and the mass fraction of phenolic resin is 3.5%; the further obtained mixture is placed in a ball mill for ball milling again for 6 hours, the speed of the ball mill is 200r / min, and the ball-to-material ratio is 3:1.

[0079] The material is cold isostatically pressed by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine is 180 MPa and the holding time is 5 minutes; the material after cold isostatic pressing is hot pressed by a hot pressing machine, wherein the hot pressing temperature of the hot pressing machine is 1500°C, the hot pressing pressure is 50 MPa, and the holding time is 1.5 hours. During the hot pressing process, argon atmosphere protection is adopted.

[0080] The hot-pressed green body is placed in a tubular furnace and pre-sintered at low temperature under an argon atmosphere, wherein the pre-sintering temperature of the tubular furnace is 800°C and the holding time is 2 hours; the pre-sintered green body is placed in a hot isostatic pressing sintering furnace and sintered at high temperature under an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace, wherein the sintering temperature of the hot isostatic pressing sintering furnace is 1800°C, the pressure is 100MPa, and the holding time is 4 hours. During the high-temperature sintering process, argon atmosphere protection is adopted. During the green body pre-sintering and high-temperature sintering process, the magnetic field generating device generates a magnetic field with a magnetic field strength of 0.5 Tesla.

[0081] The cooled material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 100 keV and the dose is 1×10¹ 7 ions / cm², and finally a fiber-reinforced metal-ceramic material is obtained.

[0082] Embodiment 2

[0083] The silicon carbide fiber was immersed in a 10% hydrofluoric acid solution for 30 minutes; the silicon carbide fiber after immersion was thoroughly rinsed with deionized water, and then the silicon carbide fiber was placed in an oven and dried at 80°C for 2 hours; the silicon carbide fiber after drying was placed in a chemical vapor deposition furnace, and trichloromethylsilane (MTS) and hydrogen were used as reaction gases for chemical vapor deposition at a high temperature of 1150°C for 2 hours, and the gas flow ratio of trichloromethylsilane (MTS) to hydrogen was 1:10; the molar ratio of 1:10:5 was used to prepare the silicon carbide fiber. A sol solution containing tetraethyl orthosilicate, ethanol and water is placed, and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 1 hour, and then dried in air for 11.5 hours, and then heat-treated at a temperature of 630°C, and the steps of immersion, drying and heat treatment are repeated 3 times; the silicon carbide fiber coated with silicon carbide coating and silicon dioxide coating is placed in a tubular furnace, and high-temperature annealing treatment is performed in an argon atmosphere, the high-temperature annealing temperature is 1000°C, and the insulation time is 2 hours; the silicon carbide fiber after high-temperature annealing is ground into silicon carbide fiber particles.

[0084] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is placed in a ball mill for ball milling, the ball milling time is 11.5 hours, the speed of the ball mill is 300 r / min, and the ball-to-material ratio is 5:1; the metal ceramic powder and silicon carbide fiber particles are placed in an ultrasonic mixer for mixing, the volume fraction of the metal ceramic powder is 81%, the volume fraction of the silicon carbide fiber particles is 19%, the mixing time is 1.1 hours, and the ultrasonic power of the ultrasonic mixer is 1100 W; polyvinyl alcohol and phenolic resin are added to the obtained mixture, the mass fraction of the mixture is 96%, the mass fraction of polyvinyl alcohol is 1.5%, and the mass fraction of phenolic resin is 2.5%; the further obtained mixture is placed in a ball mill for ball milling again for 6.5 hours, the speed of the ball mill is 220 r / min, and the ball-to-material ratio is 3:1.

[0085] The material was cold isostatically pressed by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine was 195 MPa and the holding time was 6 minutes; the material after cold isostatic pressing was hot pressed by a hot pressing machine, wherein the hot pressing temperature of the hot pressing machine was 1550°C, the hot pressing pressure was 52 MPa, and the holding time was 1.8 hours. During the hot pressing process, argon atmosphere protection was used.

[0086] The hot-pressed green body is placed in a tubular furnace and pre-sintered at low temperature under an argon atmosphere, wherein the pre-sintering temperature of the tubular furnace is 850°C and the holding time is 2.2 hours; the pre-sintered green body is placed in a hot isostatic pressing sintering furnace and sintered at high temperature under an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace, wherein the sintering temperature of the hot isostatic pressing sintering furnace is 1900°C, the pressure is 110MPa, and the holding time is 4.5 hours. During the high-temperature sintering process, argon atmosphere protection is adopted. During the green body pre-sintering and high-temperature sintering process, the magnetic field generating device generates a magnetic field with a magnetic field strength of 1.2 Tesla.

[0087] The cooled material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 105keV and the dose is 1×10¹ 7 ions / cm², and finally a fiber-reinforced metal-ceramic material is obtained.

[0088] Embodiment 3

[0089] The silicon carbide fiber was immersed in a 12% hydrofluoric acid solution for 35 minutes; the silicon carbide fiber after immersion was thoroughly rinsed with deionized water, and then the silicon carbide fiber was placed in an oven and dried at 90°C for 2.2 hours; the silicon carbide fiber after drying was placed in a chemical vapor deposition furnace, and trichloromethylsilane (MTS) and hydrogen were used as reaction gases for chemical vapor deposition at a high temperature of 1300°C for 3 hours, and the gas flow ratio of trichloromethylsilane (MTS) to hydrogen was 1:12; the molar ratio of 1:12:6 was used to prepare the silicon carbide fiber. A sol solution containing tetraethyl orthosilicate, ethanol and water is placed, and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 1.5 hours, and then dried in air for 13 hours, and then heat treated at a temperature of 680°C, and the steps of immersion, drying and heat treatment are repeated 4 times; the silicon carbide fiber coated with silicon carbide coating and silicon dioxide coating is placed in a tubular furnace, and high-temperature annealing treatment is performed in an argon atmosphere, the high-temperature annealing temperature is 1050°C, and the insulation time is 2.3 hours; the silicon carbide fiber after high-temperature annealing is ground into silicon carbide fiber particles.

[0090] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is placed in a ball mill for ball milling, the ball milling time is 12 hours, the speed of the ball mill is 330r / min, and the ball-to-material ratio is 5.5:1; the metal ceramic powder and silicon carbide fiber particles are placed in an ultrasonic mixer for mixing, the volume fraction of the metal ceramic powder is 82%, the volume fraction of the silicon carbide fiber particles is 18%, the mixing time is 1.2 hours, and the ultrasonic power of the ultrasonic mixer is 1200W; polyvinyl alcohol and phenolic resin are added to the obtained mixture, the mass fraction of the mixture is 97%, the mass fraction of polyvinyl alcohol is 1%, and the mass fraction of phenolic resin is 2%; the further obtained mixture is placed in a ball mill for ball milling again for 7 hours, the speed of the ball mill is 250r / min, and the ball-to-material ratio is 3:1.

[0091] The material is cold isostatically pressed by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine is 210 MPa and the holding time is 7 minutes; the material after cold isostatic pressing is hot pressed by a hot pressing machine, wherein the hot pressing temperature of the hot pressing machine is 1600°C, the hot pressing pressure is 55 MPa, and the holding time is 2 hours. During the hot pressing process, argon atmosphere protection is adopted.

[0092] The hot-pressed green body is placed in a tubular furnace and subjected to low-temperature pre-sintering in an argon atmosphere, wherein the pre-sintering temperature of the tubular furnace is 900°C and the holding time is 2.5 hours; the pre-sintered green body is placed in a hot isostatic pressing sintering furnace and subjected to high-temperature sintering in an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace, wherein the sintering temperature of the hot isostatic pressing sintering furnace is 2000°C, the pressure is 120MPa, and the holding time is 5 hours. During the high-temperature sintering process, argon atmosphere protection is adopted. During the green body pre-sintering and high-temperature sintering process, the magnetic field generating device generates a magnetic field with a magnetic field strength of 2 Tesla.

[0093] The cooled material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 110 keV and the dose is 1×10¹ 7 ions / cm², and finally a fiber-reinforced metal-ceramic material is obtained.

[0094] Embodiment 4

[0095] The silicon carbide fiber was immersed in a 9% hydrofluoric acid solution for 32 minutes; the silicon carbide fiber after immersion was thoroughly rinsed with deionized water, and then the silicon carbide fiber was placed in an oven and dried at 85°C for 2 hours; the silicon carbide fiber after drying was placed in a chemical vapor deposition furnace, and trichloromethylsilane (MTS) and hydrogen were used as reaction gases for chemical vapor deposition at a high temperature of 1200°C for 2.5 hours, and the gas flow ratio of trichloromethylsilane (MTS) to hydrogen was 1:11; the molar ratio was 1:11:5. A sol solution containing tetraethyl orthosilicate, ethanol and water is prepared, and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 1.2 hours, and then dried in air for 12 hours, and then heat treated at a temperature of 650°C, and the steps of immersion, drying and heat treatment are repeated 3 times; the silicon carbide fiber coated with silicon carbide coating and silicon dioxide coating is placed in a tubular furnace and subjected to high-temperature annealing treatment in an argon atmosphere, the high-temperature annealing temperature is 1020°C, and the insulation time is 2.1 hours; the silicon carbide fiber after high-temperature annealing is ground into silicon carbide fiber particles.

[0096] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is placed in a ball mill for ball milling, the ball milling time is 11.8 hours, the speed of the ball mill is 310r / min, and the ball-to-material ratio is 5.2:1; the metal ceramic powder and silicon carbide fiber particles are placed in an ultrasonic mixer for mixing, the volume fraction of the metal ceramic powder is 81.5%, the volume fraction of the silicon carbide fiber particles is 18.5%, the mixing time is 1.15 hours, and the ultrasonic power of the ultrasonic mixer is 1150W; polyvinyl alcohol and phenolic resin are added to the obtained mixture, the mass fraction of the mixture is 96.5%, the mass fraction of polyvinyl alcohol is 1.2%, and the mass fraction of phenolic resin is 2.3%; the further obtained mixture is placed in a ball mill for ball milling again for 6.8 hours, the speed of the ball mill is 230r / min, and the ball-to-material ratio is 3:1.

[0097] The material was cold isostatically pressed by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine was 200 MPa and the holding time was 6.5 minutes; the material after cold isostatic pressing was hot pressed by a hot pressing machine, wherein the hot pressing temperature of the hot pressing machine was 1580°C, the hot pressing pressure was 53 MPa, and the holding time was 1.9 hours. During the hot pressing process, argon atmosphere protection was used.

[0098] The hot-pressed green body is placed in a tubular furnace and pre-sintered at low temperature under an argon atmosphere, wherein the pre-sintering temperature of the tubular furnace is 880°C and the holding time is 2.3 hours; the pre-sintered green body is placed in a hot isostatic pressing sintering furnace and sintered at high temperature under an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace, wherein the sintering temperature of the hot isostatic pressing sintering furnace is 1950°C, the pressure is 115MPa, and the holding time is 4.8 hours. During the high-temperature sintering process, argon atmosphere protection is adopted. During the green body pre-sintering and high-temperature sintering process, the magnetic field generating device generates a magnetic field with a magnetic field strength of 1.8 Tesla.

[0099] The cooled material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 108keV and the dose is 1×10¹ 7 ions / cm², and finally a fiber-reinforced metal-ceramic material is obtained.

[0100] Embodiment 5

[0101] The silicon carbide fiber was immersed in a hydrofluoric acid solution with a concentration of 11% for 28 minutes; the silicon carbide fiber after immersion was thoroughly rinsed with deionized water, and then the silicon carbide fiber was placed in an oven and dried at a temperature of 78°C for 1.9 hours; the silicon carbide fiber after drying was placed in a chemical vapor deposition furnace, and trichloromethylsilane (MTS) and hydrogen were used as reaction gases at a high temperature of 1050°C for 1.8 hours, and the gas flow ratio of trichloromethylsilane (MTS) to hydrogen was 1:9; the molar ratio of 1:9:4.5 was used to prepare the silicon carbide fiber. A sol solution containing tetraethyl orthosilicate, ethanol and water is placed, and the silicon carbide fiber after chemical vapor deposition is immersed in the sol solution for 0.8 hours, and then dried in air for 10.5 hours, and then heat treated at a temperature of 600°C, and the steps of immersion, drying and heat treatment are repeated twice; the silicon carbide fiber coated with silicon carbide coating and silicon dioxide coating is placed in a tubular furnace, and high-temperature annealing treatment is performed in an argon atmosphere, the high-temperature annealing temperature is 980°C, and the insulation time is 1.9 hours; the silicon carbide fiber after high-temperature annealing is ground into silicon carbide fiber particles.

[0102] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is placed in a ball mill for ball milling, the ball milling time is 11.2 hours, the speed of the ball mill is 290r / min, and the ball-to-material ratio is 4.8:1; the metal ceramic powder and silicon carbide fiber particles are placed in an ultrasonic mixer for mixing, the volume fraction of the metal ceramic powder is 80.5%, the volume fraction of the silicon carbide fiber particles is 19.5%, the mixing time is 1.05 hours, and the ultrasonic power of the ultrasonic mixer is 1050W; polyvinyl alcohol and phenolic resin are added to the obtained mixture, the mass fraction of the mixture is 95.8%, the mass fraction of polyvinyl alcohol is 1.3%, and the mass fraction of phenolic resin is 2.9%; the further obtained mixture is placed in a ball mill for ball milling again for 6.2 hours, the speed of the ball mill is 210r / min, and the ball-to-material ratio is 3:1.

[0103] The material was cold isostatically pressed by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine was 185 MPa and the holding time was 5.5 minutes; the material after cold isostatic pressing was hot pressed by a hot pressing machine, wherein the hot pressing temperature of the hot pressing machine was 1520°C, the hot pressing pressure was 51 MPa, and the holding time was 1.6 hours. During the hot pressing process, argon atmosphere protection was used.

[0104] The hot-pressed green body is placed in a tubular furnace and pre-sintered at low temperature under an argon atmosphere, wherein the pre-sintering temperature of the tubular furnace is 820°C and the holding time is 2.1 hours; the pre-sintered green body is placed in a hot isostatic pressing sintering furnace and sintered at high temperature under an argon atmosphere, and then slowly cooled to room temperature in the sintering furnace, wherein the sintering temperature of the hot isostatic pressing sintering furnace is 1850°C, the pressure is 105MPa, and the holding time is 4.2 hours. During the high-temperature sintering process, argon atmosphere protection is adopted. During the green body pre-sintering and high-temperature sintering process, the magnetic field generating device generates a magnetic field with a magnetic field strength of 1.5 Tesla.

[0105] The cooled material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 103keV and the dose is 1×10¹ 7 ions / cm², and finally a fiber-reinforced metal-ceramic material is obtained.

[0106] Comparative Example 1

[0107] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is put into a ball mill for ball milling, the ball milling time is 12 hours, the speed of the ball mill is 300 r / min, and the ball-to-material ratio is 5:1.

[0108] The ball-milled powder was subjected to cold isostatic pressing by a cold isostatic pressing machine, with the molding pressure set to 200 MPa and the holding time to 6 minutes; then the powder was subjected to hot pressing by a hot pressing machine, with the hot pressing temperature being 1550°C, the hot pressing pressure being 50 MPa, and the holding time being 1.8 hours. Argon atmosphere protection was used during the hot pressing process.

[0109] The hot-pressed green body is placed in a tubular furnace and pre-sintered at a low temperature under an argon atmosphere at a temperature of 850°C for 2 hours. The pre-sintered green body is then placed in a hot isostatic pressing furnace and sintered at a high temperature under an argon atmosphere at a temperature of 1900°C and a pressure of 110 MPa for 4.5 hours. After sintering, it is slowly cooled to room temperature in the furnace.

[0110] The sintered material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 105keV and the dose is 1×10¹ 7 ions / cm² to obtain metal ceramic materials.

[0111] Comparative Example 2

[0112] Titanium metal powder and silicon carbide ceramic powder were mixed in a mass ratio of 40:60; the mixed powder was put into a ball mill for ball milling, the ball milling time was 11 hours, the speed of the ball mill was 280 r / min, and the ball-to-material ratio was 4.5:1.

[0113] The ball-milled powder was subjected to cold isostatic pressing by a cold isostatic pressing machine, with the molding pressure set at 190 MPa and the holding time at 5.5 minutes. The powder was then subjected to hot pressing by a hot pressing machine, with the hot pressing temperature at 1500°C, the hot pressing pressure at 45 MPa, and the holding time at 1.6 hours. Argon atmosphere protection was used during the hot pressing process.

[0114] The hot-pressed green body is placed in a tubular furnace and pre-sintered at a low temperature in an argon atmosphere at 800°C for 1.8 hours. The pre-sintered green body is then placed in a hot isostatic pressing furnace and sintered at a high temperature in an argon atmosphere at 1800°C and a pressure of 100 MPa for 4 hours. After sintering, it is slowly cooled to room temperature in the furnace.

[0115] The sintered material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 100 keV and the dose is 1×10¹ 7 ions / cm² to obtain metal ceramic materials.

[0116] Comparative Example 3

[0117] Titanium metal powder and silicon carbide ceramic powder are mixed in a mass ratio of 40:60; the mixed powder is put into a ball mill for ball milling, the ball milling time is 10 hours, the speed of the ball mill is 250r / min, and the ball-to-material ratio is 4:1.

[0118] The ball-milled powder was subjected to cold isostatic pressing by a cold isostatic pressing machine, with the molding pressure set at 180 MPa and the holding time at 5 minutes. The powder was then subjected to hot pressing by a hot pressing machine, with the hot pressing temperature at 1450°C, the hot pressing pressure at 40 MPa, and the holding time at 1.5 hours. Argon atmosphere protection was used during the hot pressing process.

[0119] The hot-pressed green body is placed in a tubular furnace and pre-sintered at a low temperature under an argon atmosphere at a temperature of 750°C for 1.5 hours. The pre-sintered green body is then placed in a hot isostatic pressing furnace and sintered at a high temperature under an argon atmosphere at a temperature of 1700°C and a pressure of 90 MPa for 3.5 hours. After sintering, it is slowly cooled to room temperature in the furnace.

[0120] The sintered material is cut and surface polished, and then nitrogen ions are implanted into the material surface by ion implantation, followed by annealing. The energy of the ion implantation is 95keV and the dose is 1×10¹ 7 ions / cm² to obtain metal ceramic materials.

[0121] The hardness, flexural strength, toughness, density and high temperature resistance of the metal ceramic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 are measured respectively, and the specific measurement results are as follows:

[0122]

[0123] It can be seen from the above table that in terms of hardness, the hardness values ​​of Examples 1 to 5 are significantly higher than those of the comparative example group. The hardness of Example 1 is 2200.25HV, the hardness of Example 5 is 2250.3HV, and the hardness of Comparative Example 3 is only 1500.1HV, with a significant difference; in the example group, the hardness also fluctuates with the change of process parameters. For example, the hardness of Example 3 is relatively high at HV2400.42. This is because during the silicon carbide fiber processing, such as the high chemical vapor deposition temperature (1300°C) and the long deposition time (3 hours), the silicon carbide coating is formed more densely and evenly on the fiber surface, which enhances the hardness of the overall material. At the same time, the ball milling parameters in this embodiment (ball milling time of 12 hours, rotation speed of 330r / min, ball-to-material ratio of 5.5:1) also make the metal ceramic powder and silicon carbide fiber particles more fully mixed, which is beneficial to improve the hardness of the material. The hardness of comparative examples one to three is relatively low and close. This is because the silicon carbide fiber is not subjected to complicated pretreatment and addition in the comparative examples. Only conventional operations such as molding and sintering are performed after the titanium metal powder and silicon carbide ceramic powder are mixed. The reinforcing effect of silicon carbide fiber and related coating treatment steps are lacking. The microstructure of the material is relatively loose and the bonding force between the particles is weak, resulting in lower hardness.

[0124] In terms of flexural strength, the flexural strength of Examples 1 to 5 is at a relatively high level as a whole, with the flexural strength of Example 1 being 850.32 MPa, and that of Example 5 being 860.4 MPa, and the differences between the examples being relatively small; this is because the addition of silicon carbide fibers has a good reinforcing effect; the fibers can effectively transfer stress in the material and prevent the expansion of cracks, thereby improving the flexural strength of the material; at the same time, the process parameters in the process of mixing powders, molding, sintering, etc. in the example group are relatively optimized, such as the reasonable setting of ball milling time and rotation speed, which makes the powder particles refined and mixed evenly, and can form a good bonding interface during the sintering process, further improving the flexural performance of the material; the flexural strength of Comparative Examples 1 to 3 is significantly lower than that of the example group; the flexural strength of Comparative Example 3 is only 650.18 MPa, which is quite different from that of the example group; this is because the comparative example does not utilize silicon carbide fibers for reinforcement and toughening, and the molding and sintering processes are relatively not sophisticated enough, resulting in more defects and pores inside the material, which is prone to breakage when subjected to bending stress, resulting in lower flexural strength.

[0125] In terms of toughness, the toughness of Examples 1 to 5 is relatively stable, with the toughness of Example 1 being 12.55 MPa・m^1 / 2 and the toughness of Example 5 being 12.88 MPa・m^1 / 2; the presence of silicon carbide fiber is a key factor in improving toughness; when the material is subjected to external force, the fiber can absorb energy through mechanisms such as pull-out and fracture, prevent the rapid expansion of cracks, and thus improve the toughness of the material; in addition, the surface treatment of the silicon carbide fiber in the embodiment group, such as chemical vapor deposition and sol solution immersion, improves the interface bonding between the fiber and the matrix, and further improves the toughness of the material; the toughness of Comparative Examples 1 to 3 is relatively low, with the toughness of Comparative Example 3 being only 8.88 MPa・m^1 / 2; due to the lack of toughening effect of silicon carbide fiber, and the fact that effective measures may not be taken to improve the microstructure and interface properties of the material during the preparation process, the material has poor toughness and is more susceptible to brittle fracture when subjected to external force impact.

[0126] In terms of density, the densities of Examples 1 to 5 are relatively high, all above 98%, and the density of Example 2 reaches 98.5%; this is due to the various process means adopted in the example group; in the process of silicon carbide fiber processing, chemical vapor deposition and sol solution treatment and other steps make the bonding between the fiber and the matrix closer, reducing the presence of pores; at the same time, in the molding and sintering process, reasonable process parameters (such as cold isostatic pressing pressure, hot pressing molding temperature and pressure, sintering temperature and pressure, etc.) also contribute to the densification of the material and improve the density of the material; the density of Comparative Examples 1 to 3 is relatively low, between 95.50% and 96.50%; the silicon carbide fiber is not specially treated in the comparative examples, and there are some deficiencies in the molding and sintering processes, resulting in more pores and defects inside the material, resulting in lower density; lower density will affect the mechanical properties and other properties of the material, such as hardness, flexural strength and high temperature resistance.

[0127] In terms of high temperature resistance, the high temperature resistance of embodiments one to five is significantly better than that of the comparative example group; the high temperature resistance of embodiment one is 1600.50℃, the high temperature resistance of embodiment five is 1620.55℃, and the high temperature resistance of comparative example three is only 1150.3℃; silicon carbide fiber itself has good high temperature resistance and plays a key role in the material; the treatment of silicon carbide fiber in the embodiment group and the high temperature and argon atmosphere protection adopted during the sintering process enable the material to maintain good structural stability at high temperatures; in addition, the high density of the material also helps to improve its high temperature resistance, reduce the intrusion of gas and impurities at high temperatures, thereby improving the high temperature resistance limit of the material; the high temperature resistance of comparative examples one to three is poor; due to the lack of reinforcement of silicon carbide fiber and the relatively simple process during the preparation process, the structure of the material is prone to change at high temperatures, such as grain growth, phase transition, etc., resulting in a decrease in the performance of the material and a decrease in high temperature resistance.

[0128] In addition, in none of the comparative examples 1 to 3, the silicon carbide fiber is pretreated. The examples 1 to 5 can remove the impurities and natural oxide layer on the surface of the silicon carbide fiber through acid etching, making the fiber surface rough, thereby increasing the bonding force between the subsequent coating and the fiber. The moisture on the fiber surface can be removed through drying treatment to prevent adverse effects such as pores and cracks in subsequent high-temperature processes such as chemical vapor deposition; silicon carbide coatings and silicon dioxide coatings can be formed on the surface of the silicon carbide fiber through chemical vapor deposition and sol-gel treatment, further enhancing the performance of the fiber, improving its bonding ability with the matrix material, and at the same time improving the high temperature resistance and other properties of the fiber; high-temperature annealing treatment can eliminate the internal stress in the coating, making the coating structure more stable and improving the overall performance of the fiber; grinding treatment can better mix with metal ceramic powder, so that the fiber is evenly distributed in the material, thereby effectively playing a reinforcing role. Through the above-mentioned pretreatment process, the comprehensive performance of the fiber-reinforced metal ceramic material prepared in examples 1 to 5 can be made much higher than the comprehensive performance of the ordinary metal ceramic material prepared in comparative examples 1 to 3.

[0129] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.

[0130] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0131] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0132] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.

[0133] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.

Claims

1. A method for preparing a fiber-reinforced metal-ceramic material, characterized in that: The preparation method comprises: S1: pretreating silicon carbide fibers and finally obtaining silicon carbide fiber particles; Step S1 specifically includes: S11: soaking the silicon carbide fiber in a hydrofluoric acid solution; S12: After the soaking, the silicon carbide fiber is thoroughly rinsed with deionized water, and then dried; S13: placing the dried silicon carbide fiber in a chemical vapor deposition furnace, and performing chemical vapor deposition at a high temperature using trichloromethylsilane and hydrogen as reaction gases to deposit a silicon carbide coating on the surface of the silicon carbide fiber; S14: preparing a sol solution containing tetraethyl orthosilicate, ethanol and water in a predetermined ratio, soaking the silicon carbide fiber after chemical vapor deposition in the sol solution, and then drying and heat treating to convert the sol into a silicon dioxide coating, wherein in step S14, the soaking step to the heat treatment step are repeated 2-4 times; S15: placing the silicon carbide fiber coated with the silicon carbide coating and the silicon dioxide coating into a tube furnace and performing a high temperature annealing treatment in an argon atmosphere; S16: grinding the silicon carbide fibers after high temperature annealing into silicon carbide fiber particles; S2: mixing and grinding titanium metal powder and silicon carbide ceramic powder according to a predetermined ratio to obtain metal ceramic powder; S3: putting the metal ceramic powder and the silicon carbide fiber particles into an ultrasonic mixer for mixing; S4: adding a dispersant and a binder to the mixture obtained in step S3, mixing and grinding again; S5: performing cold isostatic pressing and hot pressing on the mixture obtained in step S4 in sequence, wherein argon gas is used as an atmosphere protection during the hot pressing process; S6: placing the hot-pressed green body into a tubular furnace and performing low-temperature pre-sintering in an argon atmosphere; S7: placing the pre-sintered green body into a hot isostatic pressing sintering furnace and sintering at high temperature under an argon atmosphere, and then slowly cooling the green body to room temperature in the sintering furnace; S8: Cut and polish the cooled material, then implant nitrogen ions into the material surface by ion implantation and perform annealing to finally obtain a fiber-reinforced metal-ceramic material.

2. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S11, the concentration of the hydrofluoric acid solution is 8-12%, and the immersion time is 25-35 minutes; In step S12, the drying temperature is 75-90°C and the drying time is 1.8-2.2 hours; In step S13, the temperature of the high temperature treatment is 1000-1300° C., the gas flow ratio of trichloromethylsilane and hydrogen is 1:(8.5-12), and the chemical vapor deposition time is 1.5-3 hours; In step S14, the molar ratio of tetraethyl orthosilicate, ethanol and water is 1:(8-12):(4-6), the soaking time is 0.5-1.5 hours, the drying time in air is 10-13 hours, and the heat treatment temperature is 580-680°C; In step S15, the high temperature annealing temperature is 950-1050°C, and the holding time is 1.8-2.3 hours.

3. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: Step S2 specifically includes: S21: mixing titanium metal powder and silicon carbide ceramic powder in a mass ratio of 40:60; S22: putting the mixed powder into a ball mill for ball milling. The ball milling time is 11-12 hours. The rotation speed of the ball mill is 280-330 r / min. The ball-to-material ratio is (4.7-5.5):

1.

4. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S3, the volume fraction of the metal ceramic powder is 80-82%, the volume fraction of the silicon carbide fiber particles is 18-20%, the mixing time of the metal ceramic powder and the silicon carbide fiber particles in the ultrasonic mixer is 1-1.2 hours, and the ultrasonic power is 1000-1200W.

5. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S4, the mass fraction of the mixture obtained in step S3 is 95.5-97%, the mass fraction of the dispersant is 1-1.5%, and the mass fraction of the binder is 2-3%, wherein the dispersant is polyvinyl alcohol and the binder is phenolic resin; Step S4 specifically includes: S41: adding a dispersant and a binder to the mixture obtained in step S3; S42: The mixture obtained in step S41 is put into a ball mill and ball milled again for 6-7 hours. The rotation speed of the ball mill is 200-250 r / min and the ball-to-material ratio is 3:

1.

6. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S5, the mixture obtained in step S4 is subjected to cold isostatic pressing by a cold isostatic pressing machine, wherein the set molding pressure of the cold isostatic pressing machine is 180-210 MPa and the holding time is 5-7 minutes; and / or, In step S5, a hot pressing molding machine is used to hot press the material after cold isostatic pressing, wherein the hot pressing temperature of the hot pressing molding machine is 1500-1600° C., the hot pressing pressure is 50-55 MPa, and the insulation time is 1.5-2 hours.

7. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S6, the pre-sintering temperature of the tube furnace is 800-900° C., and the holding time is 2-2.5 hours; and / or, In step S7, the sintering temperature of the hot isostatic pressing furnace is 1800-2000°C, the pressure is 100-120 MPa, and the holding time is 4-5 hours.

8. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1 or 7, characterized in that: A magnetic field generating device is provided in both the tubular furnace and the hot isostatic pressing sintering furnace. During the pre-sintering and high-temperature sintering of the green body, the magnetic field intensity generated by the magnetic field generating device is 0.5-2 Tesla.

9. The method for preparing a fiber-reinforced metal-ceramic material according to claim 1, characterized in that: In step S8, the energy of the ion implantation is 100-110 keV and the dose is 1×10¹ 7 ions / cm².

Citation Information

Patent Citations

  • SiCf / SiC ceramic-based composite material with composite interface and preparation method of SiCf / SiC ceramic-based composite material

    CN109553430A

  • High-toughness and high-wear-resistance titanium carbonitride-based cermet material and preparation method thereof

    CN111519115A